An antimalarial neem leaf extract has both schizonticidal and gametocytocidal activities - Udeinya, J.I.; Shu, E.N.; Quakyi, I.A.; Ajayi, F.O. (American Journal of Therapeutics, 2008)
A crude acetone/water (50/50) extract of neem leaves (IRAB) was evaluated for activity against the asexual (trophozoites/schizonts) and the sexual (gametocytes) forms of the malarial parasite, Plasmodium falciparum, in vitro. In separate 72 hour cultures of both asexual parasites and mature gametocytes treated with IRAB (0.5 μg/mL), parasite numbers were less than 50% of the numbers in control cultures, which had 8.0% and 8.5% parasitemia, respectively. In cultures containing 2.5 μg/mL, asexual parasites and mature and immature gametocytes were reduced to 0.1%, 0.2%, and 0% parasitemia, respectively. There were no parasites in the cultures containing 5.0 μg/mL. This extract, if found safe, may provide materials for development of new antimalarial drugs that may be useful both in treatment of malaria as well as the control of its transmission through gametocytes. © 2008 Lippincott Williams & Wilkins, Inc.
Keywords: Antimalarial; Gametocytocidal; Malaria; Neem leaf extract; Schizonticidal; EMTREE drug terms: Azadirachta indica extract; EMTREE medical terms: article; controlled study; drug activity; drug effect; gametocyte; in vitro study; nonhuman; parasitemia; plant leaf; Plasmodium falciparum; priority journal; schizont; trophozoite; MeSH: Animals; Antimalarials; Azadirachta; Cells, Cultured; Dose-Response Relationship, Drug; Gametogenesis; Plant Extracts; Plant Leaves; Plasmodium falciparum; Reproduction; Schizonts